β-Hydroxy carbocation intermediates in solvolyses of di- and tetra-hydronaphthalene substrates - Kudavalli, Jaya S.; More O'Ferrall, Rory A. (Beilstein Journal of Organic Chemistry, 2010)
Solvolysis of trichloroacetate esters of 2-methoxy-1,2-dihydro-1-naphthols shows a remarkably large difference in rates between the cis and trans isomers, kcis/ktrans = 1800 in aqueous acetonitrile. This mirrors the behaviour of the acid-catalysed dehydration of cis- and trans-naphthalene-1,2-dihydrodiols to form 2-naphthol, for which kcis/ktrans = 440, but contrasts with that for solvolysis of tetrahydronaphthalene substrates, 1-chloro-2-hydroxy-1,2,3,4-tetrahydronaphthalenes, for which kcis/ktrans = 0.5. Evidence is presented showing that the trans isomer of the dihydro substrates reacts unusually slowly rather than the cis isomer unusually rapidly. Comparison of rates of solvolysis of 1-chloro-1,2,3,4-tetrahydronaphthalene and the corresponding (cis) substrate with a 2-hydroxy group indicates that a β-OH slows the reaction by nearly 2000-fold, which represents a typical inductive effect characteristic also of cis-dihydrodiol substrates. The slow reaction of the trans-dihydrodiol substrate is consistent with initial formation of a β-hydroxynaphthalenium carbocation with a conformation in which a C–OH occupies an axial position β to the carbocation centre preventing stabilisation of the carbocation by C–H hyperconjugation, which would occur in the conformation initially formed from the cis isomer. It is suggested that C–H hyperconjugation is particularly pronounced for a β-hydroxynaphthalenium ion intermediate because the stability of its no-bond resonance structure reflects the presence of an aromatic naphthol structure.
Keywords: aromaticity; β-hydroxycarbocations; hyperconjugation; solvolysis